Figurative expressive means as a subject of comparative study (based on L. Durrell’s “Balthazar” and its French translation) - Ayunts, Anoush (Bulletin of Yerevan University B: Philology, 2025)
In this article, the study is carried out within the framework of hermeneutics understood as a comprehensive method of philological analysis of a work of verbal creativity. As the art of interpretation, philological hermeneutics aims to uncover both the content and the expressive layers of a literary work. The goal of the article is to explore the aesthetic impact of figurative expressive means present in a work of literature by conducting a comparative analysis of the original and its translation. In this framework, the translation is treated as a parallel text, whose comparison with the original enables to identify expressive and aesthetic elements that might otherwise go unnoticed if examined within the framework of a single linguistic context. The study focuses on the English original of Lawrence Durrell’s “Balthazar” and its French translation. Through detailed analysis of examples, the article demonstrates that the full potential of figurative expressive means is most effectively revealed through comparative analysis. Moreover, comparing the translation with the original not only highlights the figurative richness of expressive means in the source text but also enhances their aesthetic impact upon the reader. It stands to reason to believe that the effective realization of the goal set in the present article will contribute to the solution of the all important linguistic problem of understanding and interpreting a work of Verbal art.
Keywords: Verbal Art; philological hermeneutics; figurative expressive means; comparative study; interpretation of a work of verbal creativity; Lawrence Durrell; “Balthazar”